Exergetic and ecological performance analyses of a gas turbine system with two intercoolers and two re-heaters - Gonca, Guven (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
In this study, performance analyses of a gas turbine with two intercoolers and two re-heaters based on energetic, exergetic and ecological concepts such as power, power density, second-law efficiency (exergy efficiency), exergy destruction, ecological coefficient of performance (ECOP) and effective ecological power density (EFECPOD). The effects of turbine design parameters such as turbine speed, air mass flow rate, equivalence ratio, pressure ratio, turbine diameter, turbine length, heat transfer coefficient, residual gas fraction, turbine wall temperature, inlet pressure and inlet temperature on the performance characteristics have been investigated by taking temperature-dependent specific heats and heat transfer losses into consideration. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Joule-Brayton cycle; Gas turbine system; Power density; ECOP; Exergy; EFECPOD; IRREVERSIBLE MILLER CYCLE; ARTIFICIAL NEURAL-NETWORK; BRAYTON CYCLE; REGENERATIVE BRAYTON; THERMODYNAMIC ANALYSIS; MAXIMUM POWER; HEAT-TRANSFER; EFFICIENCY OPTIMIZATION; PARAMETRIC ANALYSIS; ENGINE DACE; Thermodynamics; Energy & Fuels